2001
DOI: 10.1111/j.1752-1688.2001.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN ACCUMULATION IN A CONSTRUCTED WETLAND FOR DAIRY WASTEWATER TREATMENT1

Abstract: : A free water surface (FWS) constructed wetland was installed at a dairy in Glendale, Arizona, to study the potential of such a wetland to remove nitrogen (N) from wastewater. The study objectives were: (1) to determine N removal from the wastewater, and (2) to evaluate N accumulation in soil and plant tissues. The system consisted of eight cells (70 × 9 × 1.5 m) planted with Typha domingensis, Scirpus validus, and Phragmites australis. The four cells in series were lined with plastic, and the four cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, it is worth noting that an average pH value of 7.1 ± 0.4 and DO concentration of 4.2 ± 2.1 mg L −1 in the influent are favorable for effective nitrification. According to Shamir , the optimum pH for nitrification is between 7.2 and 9.0, and nitrification rate decreases significantly below pH 6. Also, Shamir reported that DO concentrations between 0.3 and 2 mg L −1 are the threshold values for effective nitrification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is worth noting that an average pH value of 7.1 ± 0.4 and DO concentration of 4.2 ± 2.1 mg L −1 in the influent are favorable for effective nitrification. According to Shamir , the optimum pH for nitrification is between 7.2 and 9.0, and nitrification rate decreases significantly below pH 6. Also, Shamir reported that DO concentrations between 0.3 and 2 mg L −1 are the threshold values for effective nitrification.…”
Section: Resultsmentioning
confidence: 99%
“…According to Shamir , the optimum pH for nitrification is between 7.2 and 9.0, and nitrification rate decreases significantly below pH 6. Also, Shamir reported that DO concentrations between 0.3 and 2 mg L −1 are the threshold values for effective nitrification. Influent DO concentrations in this study were well above these suggested values.…”
Section: Resultsmentioning
confidence: 99%
“…High-ammonia nitrogen water sources include animal feed lot slurries (Ham, 2002), and centrate from biosolids processing (Jeavons et al, 1998). These sources can contain up to 1000 mg/l ammonia nitrogen and may be discharged into artificially established riparian (Hubbard et al, 1998) and wetland (Samir et al, 2001) receiving systems. Clarke and Baldwin (2002) tested the ammonia nitrogen tolerance of four emergent wetland species at levels of 0-400 mg/l ammonia-N under flooded and nonflooded conditions.…”
Section: Ammonia Toxicitymentioning
confidence: 99%
“…Toxicity may actually be due to release of ammonia gas into the water, as un-ionized ammonia was inhibitory to growth of rice and duckweed in aquatic systems at less than 10 mg/l (Wang, 1991). As long as the ammonia nitrogen concentration is kept below toxic levels, wetland and riparian plants can be used to remove nitrogen from effluent water (Hubbard et al, 1998;Samir et al, 2001). Hence, it is important to determine the critical levels of ammonia nitrogen for growth and toxicity to candidate species in constructed receiving systems, such as wetlands or buffer strips.…”
Section: Ammonia Toxicitymentioning
confidence: 99%
“…The soil in CWs has been proved to be a major sink for N. However, although data on the influent and effluent N concentrations are often explicitly available; data on the N accumulation (DON, TN, NH 4 + or NO 3 − -N) within the soil profile of various CWs are scarce. Shamir et al (2001) measured 30-40 % N accumulation in soil of the total accumulated N in a clay-lined surface flow CWs system of which about 80 % of the total N accumulated was organic and the remainder was NH 4 + . The N accumulation decreased with soil depth, with 42-48 % in the upper 0.15 m and 20-24 % in deeper layers.…”
Section: Accumulation Of C and N In Cws Soilsmentioning
confidence: 99%